Sistemas de controle gerencial nas cooperativas de crédito: estudo de casos - Mallmann, Carla (2018)
The present research had as general objective to identify the characteristics of the systems of managerial control in the Credit Cooperatives. Thus, for the accomplishment of this research was used the method of the multiple case study and the qualitative approach. Data were collected through semi-structured interviews and document searches. The objects of this research were the Credit Cooperatives located in the states of Rio Grande do Sul and Rio de Janeiro. As the main characteristics of the control systems, it was observed that the culture of cooperatives is strongly linked to the cooperative principles, which also reflects in its management form. For the monitoring and control of the performance of the cooperative and employees, the cooperatives have mostly used their own systems. It is also noticed the concern to maintain a harmonious relationship of the direction with the collaborators, being the goals proposed in a harmonious way and the employees participating in the elaboration of the planning and budget, in the majority of the cooperatives. As a form of reward, cooperatives offer a number of benefits, a career plan and incentives for employee training. Regarding its governance, IBGC governance principles can be observed in its day-to-day and in the form of management, while the guidelines of good practices created by the BACEN are still being implemented. The control addressed in this research has a more behavioral focus, incorporating non-financial variables, and the human context being considered. Thus, considering all the control tools used by cooperatives and their management, it is concluded that credit cooperatives are very close to the literature presented in this research.